Pharmacotherapy for acute myocardial infarction - Kim, Sung Soo; Kim, Hyun Kuk (Taehan Ŭisa Hyŏphoe chi, 2021)
Clinical practice guidelines published by the European Society of Cardiology and the American College of Cardiology/ American Heart Association provide recommendations based on evidence, including randomized controlled trials and registry data, for clinicians to enable efficient clinical decision-making and improve prognosis for patients with acute myocardial infarction (AMI). However, there are several differences in practice, health systems, and races between Korea and Western countries; further, many studies on pharmacotherapy were conducted in the prepercutaneous coronary intervention era. An expert consensus document on pharmacotherapy for AMI was recently published following demands for the establishment of Korean guideline reflecting data in the modern percutaneous coronary intervention era. In this review, we summarized AMI guidelines from Europe, America, Japan, and Korea, and analyzed studies on pharmacotherapy for AMI including well-organized randomized controlled trials by Korean researchers and large-sized registry datasets, such as the Korea Acute Myocardial Infarction Registry and the Korean National Health Insurance Service.